Special Surface Finds from Old Wibil, an Iron Age Site in Ar Rustaq, Sultanate of Oman - Douglas, Khaled; Gernez, Guillaume; Hesein, Mohamad A. (The Journal of Oman Studies, 2025)
This paper presents a study of two archaeological objects that were found by the research team on the surface of the Old Wabel, located on the northern borders of the city of Ar Rustaq, during an inspection visit to the site, which recently faced a massive bulldozing movement that destructed large part of it. The pottery scattered densely on the surface indicates that the site dates back to the Early Iron Age. One of these two pieces represents a part of a clay anthropomorphic figurine of a naked standing woman. Only the upper body of it remains intact, while the head, legs, and arms are missing. This figurine is unique as it not a functional and/or decorative element of a pot like most Iron Age figurines found at different Iron Age sites in the region. Generally, most of the anthropomorphic figurine found in the Omani peninsula were associated with buildings of a ritual nature, suggesting that these figurines were used for ritual purposes. In Old Wabel, an isolated building with a distinctive architectural features was found near the figurine spot, which may have had a ritual function. The second archaeological object represents a stamped seal made from soft stone. The shape of the seal is almost parallelepipedic. The base on which the impression is made is wider than the heel, which is slightly narrower and more rounded. The other sides are flat and regular. The deep incisions that mark the seal pattern consist of two median longitudinal lines, around which radiate oblique lines and three circular cups. It is very difficult to recognize a motif, although it may be a highly stylized human figure. The existence of a seal near the distinctive building might support the interpretation of the team of the Ar Rustaq-Batinah Archaeological Survey project (RBAS) as a communal building.